PENGARUH SIFAT MACHIAVELLIAN, LOCUS OF CONTROL INTERNAL, DAN PROFESIONALISME PADA EFEKTIVITAS PERSETUJUAN KREDIT DI PT. BANK NEGARA INDONESIA (PERSERO), TBK. WILAYAH DENPASAR - Pandita, Ida Bagus Yoga; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
This research aims to get empirical evidence about the effect of Machiavellian characteristics , internal locus of control and professionalism approval effectiveness of the credits. This study is implement the technic of multiple linear regression analysis. The population that utilized for this analysis are the entire credit analysits of PT Bank Negara Indonesia (Persero), Tbk. Denpasar which using purposive sampling as the sampling method. Questionnaires are used as an instrument in the data compilation from respondents. Total samples that had been researched are 97 respondents. Based on the result from the research that had been conducted, Machiavellian characteristics is providing a negative influence in the approval effectiveness of the credit. On the other hand, internal locus of control is presenting a positive impact on the approval effectiveness of the credit.
Keywords: Machiavellian characteristics, locus of control, professionalism, approval effectiveness of the credits